The Matter of Architecture as Artwork - Francesco Gurrieri (Agathón)
The article, after some references to different opinions on the current restoration field, dwells on the natural matter used in architecture as valuable historic artwork; aiming to preservation and reintegration in the Restoration of Monuments.